1996
DOI: 10.1074/jbc.271.31.18326
|View full text |Cite
|
Sign up to set email alerts
|

Reengineering the Nucleotide Cofactor Specificity of the RecA Protein by Mutation of Aspartic Acid 100

Abstract: The RecA protein of Escherichia coli (M r 37,842, 352 amino acids) is essential for homologous genetic recombination and for the postreplicative repair of damaged DNA. The purified RecA protein will promote a variety of DNA pairing reactions that presumably reflect in vivo recombination functions. The most extensively investigated DNA pairing activity is the ATPdependent three-strand exchange reaction, in which a circular ssDNA 1 molecule and a homologous linear dsDNA molecule are recombined to yield a nicked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
23
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 13 publications
6
23
0
Order By: Relevance
“…Nevertheless, previous studies performed to analyze RecA-cofactor and RecA-DNA interactions have demonstrated the potential power of this approach. For example, Trp replacement of His163 in loop 1 of the RecA protein allowed the formation and conformational dynamics of RecA-ATP␥S filaments to be monitored by real-time spectrofluorometry (15)(16)(17). In addition, mutant proteins such as F203W (12) and Y65W (18) report DNA binding, while Y264W and Y103W (19,20) report binding ATP as well as DNA.…”
mentioning
confidence: 98%
“…Nevertheless, previous studies performed to analyze RecA-cofactor and RecA-DNA interactions have demonstrated the potential power of this approach. For example, Trp replacement of His163 in loop 1 of the RecA protein allowed the formation and conformational dynamics of RecA-ATP␥S filaments to be monitored by real-time spectrofluorometry (15)(16)(17). In addition, mutant proteins such as F203W (12) and Y65W (18) report DNA binding, while Y264W and Y103W (19,20) report binding ATP as well as DNA.…”
mentioning
confidence: 98%
“…Addition of ATP, ATP␥S, or dATP results in a conformation change to an active form that is manifested by extended filaments on DNA with a pitch of 95 Å (41)(42)(43)(44)(45)(46)(47)(48)(49) A, in the 3-strand reaction, a RecA filament is formed on the circular ssDNA. The linear duplex DNA is then aligned with the bound single strand, and exchange is initiated to form a branched intermediate.…”
mentioning
confidence: 99%
“…Recently, several reports from the Bryant laboratory have shown that binding of a nucleoside triphosphate cofactor to RecA protein bound to ssDNA causes an isomerization of the protein from the inactive to the active form (18,24,36,37). They further showed that the ability of a nucleoside triphosphate cofactor to induce an isomerization in RecA protein to the active form is dependent on the S 0.5 value for that cofactor: the nucleoside triphosphate cofactors whose S 0.5 value is 100-120 µM or lower are capable of stabilizing the strand exchange-active conformation of RecA protein.…”
Section: Discussionmentioning
confidence: 99%
“…Menetski et al demonstrated that all of the nucleoside triphosphate cofactors that are hydrolyzed by RecA protein are able to induce the high-affinity ssDNA binding state of the RecA, which is the active form of the protein (22). A more recent series of papers from the Bryant laboratory has shown that the ability of a nucleoside triphosphate cofactor to stabilize the active conformation of RecA protein in DNA strand exchange is directly related to the S 0.5 for that cofactor (where S 0.5 is the substrate concentration required for half-maximal velocity) (18,24,36,37). Only the nucleoside triphosphate cofactors whose S 0.5 value is 100-120 µM or lower are capable of stabilizing the strand exchange-active conformation of RecA protein.…”
mentioning
confidence: 99%